Analisis Risiko Supply Chain pada Material Part Joint Brake Rod di PT XYZ - Wagiana Rohmah; Wahyudin Wahyudin; Zaskya Indah Vindari; Adinda Gita Azzahra; Samitha Pujia Khan; Sekar Mustika Ayuningtyas (Fakultas Teknik, 2023)
PT XYZ is a local company engaging in the production of metal stamping parts, tools, and dies that serve product requests from domestic and international multinational companies as customers of this company. In its supply chain system, the company is still experiencing problems with the arrival of the brake rod joint part material that is not on time. This study aims to identify and analyze risks in the supply chain material part joint brake rod using the failure mode and effect analysis (FMEA) method. The use of the FMEA method to determine the level of risk priority that has been identified based on the RPN value. The identification results obtained a total of 12 risks on the part of suppliers, storage of raw materials, and the production process. The highest priority risk is on the supplier side where there are delays from importers and loading shearing is overloaded as indicated by an RPN value of 90. In addition, inaccuracy in the shearing process is the second highest priority risk with an RPN value of 50. So, it is necessary to make improvements to the highest priority risk by evaluating supplier performance.